Clinical Effectiveness of Training for Awareness Resilience and Action Online Compared to Standard Treatment for Adolescents and Young Adults With Depression: Study Protocol and Analysis Plan for a Pragmatic, Multi-Center Randomized Controlled Superiority Trial - Ekbäck, Erik; Granåsen, Gabriel; Svärling, Rachel; Blomqvist, Ida; Henje, Eva (Frontiers in Psychiatry, 2021)
Depression in adolescents and young adults is an increasing global health concern. Available treatments are not sufficiently effective and relapse rates remain high. The novel group-treatment program “Training for Awareness, Resilience and Action” (TARA) targets specific mechanisms based on neuroscientific findings in adolescent depression. TARA is framed within the National Institute of Mental Health´s Research Domain Criteria and has documented feasibility and preliminary efficacy in the treatment of adolescent depression. Since neurodevelopment continues well into the mid-twenties, age-adapted treatments are warranted also for young adults. Patients 15-22 years old, with either major depressive disorder (MDD) or persistent depressive disorder (PDD) according to the DSM-IV/5 or a rating >40 on the clinician rating scale Children's Depression Rating Scale - Revised (CDRS-R), will be recruited from specialized Child and Adolescent Psychiatry and local Youth-Clinics and randomized to either TARA or standard treatment, including but not limited to antidepressant medication and/or psychotherapy. Outcome measures will be obtained before randomization (T0), after three months of treatment (T1) and at six-months- (T2) and 24-months- (T3) follow-up. Additionally, dose-response measures will be obtained weekly in the TARA-arm and measures for mediation-analysis will be obtained halfway through treatment (T0,5). Primary outcome measure is Reynolds Adolescent Depression Scale (RADS-2) score at T1. Secondary outcome measures include RADS-2 score at T2, Multidimensional Anxiety Scale for Children at T1 and T2, and CDRS-R at T1. Additional outcome measures include self-report measures of depression-associated symptoms, systemic bio-indicators of depression from blood and hair, heartrate variability, brain magnetic resonance imaging, as well as three-axial accelerometry for sleep-objectivization. Qualitative data will be gathered to reach a more comprehensive understanding of the factors affecting adolescents and young adults with depression and the extent to which the different treatments address these factors. In summary, this article describes the design, methods and statistical analysis plan for pragmatically evaluating the clinical effectiveness of TARA. This will be the first RCT to examine the effects of TARA compared to standard treatment for adolescents and young adults with MDD or PDD. We argue that this study will extend the current knowledgebase regarding the treatment of depression. NCT-registry number: NCT04747340